1987
DOI: 10.1017/s0043174500053856
|View full text |Cite
|
Sign up to set email alerts
|

Interaction BetweenColletotrichum coccodesand Thidiazuron for Control of Velvetleaf (Abutilon theophrasti)

Abstract: Velvetleaf (Abutilon theophrastiMedik. # ABUTH) is difficult to control with existing weed control strategies. Some measure of control can be obtained with a fungus,Colletotrichum coccodes(Wallr.) Hughes, used as a bioherbicide, but when the bioherbicide application was combined with the plant growth regulator thidiazuron (N-phenyl-N′-1,2,3-thidiazol-5-yl-urea), weed control was substantially improved. Thidiazuron alone interfered with normal development of velvetleaf, causing stunting and initiation of axilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 6 publications
1
32
0
Order By: Relevance
“…using the herbicide thidazuron in combination with Colletotrichum coccodes (Wallr). Hughes was noticeably less effective in field trials (Wymore et al 1987;Wymore and Watson, 1989). Reduced efficacy may often be a result of lower biocontrol performance under less favourable field environments (Leger et al 2001;Netland et al 2001;Chandramohan et al 2002) and increased tolerance of plants (Hodgson et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…using the herbicide thidazuron in combination with Colletotrichum coccodes (Wallr). Hughes was noticeably less effective in field trials (Wymore et al 1987;Wymore and Watson, 1989). Reduced efficacy may often be a result of lower biocontrol performance under less favourable field environments (Leger et al 2001;Netland et al 2001;Chandramohan et al 2002) and increased tolerance of plants (Hodgson et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…This area has been reviewed by Altman et al (1990), Christy et al (1993), Greaves and Sargent (1986), Hoagland (1996), and Lévesque and Rahe (1992). In many cases, positive interactions exist between bioherbicides and chemical herbicides (Léger et al 2001;Smith and Hallett 2003;Wymore et al 1987), and where the mechanism has been investigated, it has been shown that the chemical herbicide has predisposed the plant to attack by the plant pathogens (Sharon et al 1992). The most thoroughly characterized systems show that sublethal doses of glyphosate can inhibit the plant's ability to produce phytoalexins (Lévesque and Rahe 1992;Sharon et al 1992).…”
Section: Weeds Of Agronomic/horticultural Cropsmentioning
confidence: 99%
“…Sorsa et al (1988) also reported synergistic interactions between the herbicide endothall and the fungal pathogen Colletotrichum gloeosporioides against Eurasian watermilfoil. Moreover, many positive interactions between chemical herbicides and bioherbicides have been demonstrated in terrestrial plants (Hoagland 1996;Léger et al 2001;Smith and Hallet 2006;Wymore et al 1987).…”
Section: Resultsmentioning
confidence: 99%